Construction and validation of an educational video for human papillomavirus vaccination - Iris Nayara da Conceição Souza Interaminense; Sheyla Costa de Oliveira; Francisca Márcia Pereira Linhares; Tatiane Gomes Guedes; Vânia Pinheiro Ramos; Cleide Maria Pontes
ABSTRACT Objectives: to validate an educational video aimed at the adhesion of human papillomavirus vaccination. Methods: a methodological study, where the knowledge about the theme and the technology to be constructed in six focal groups was identified; a theoretical framework was set up and the existing videos were uploaded. After that, pre-production, production and post-production were followed. In validation of content, 22 specialists participated, and in appearance, ten adolescents, ten mothers, ten teachers and ten audiovisual professionals. Absolute frequency, Binomial Test, and Content Validity Index were used. Results: agreement was satisfactory in most items. Regarding relevance, 20 items had indices above 0.80 among judges. Assessment was positive among girls and mothers. Only three items had indices less than 0.80 among teachers and video professionals. Conclusions: the educational video was validated, conferring credibility to contribute to educational actions and improve vaccination indexes.